Komposisi Makanan Ikan Selanget, Anodontostoma chacunda, H.B. 1822 (Pisces: Clupeidae) di Perairan Pantai Mayangan, Jawa Barat - Mohammad Fadjar Rahardjo; Murniarti Brojo; Charles Parningotan Haratua Simanjuntak; Ahmad Zahid (Universitas Gadjah Mada, 2006)
The research was conducted for six months from December 2003 to May 2004 to investigate the diet composition of chacunda gizzard shad, Anodontostoma chacunda. A total of 773 fishes were captured using gillnet with mesh sizes varying from 1.5 to 3 inches. The fish samples ranged 83–170 mm in length. For food habits analysis, the index of preponderance method was used. The dominant diets in stomach contents were Coscinodiscus, Pleurosigma and Rhizosolenia. There were no differences in diet composition between males and females among the sizes, and among the months. Based on index of electivity, the result showed that the fish preferred Coscinodiscus, Pleurosigma, Rhizosolenia, Gyrosigma, Melosira, Navicula, and Copepoda.